2010
DOI: 10.1007/s00213-010-2070-x
|View full text |Cite
|
Sign up to set email alerts
|

Mephedrone (4-methylmethcathinone; ‘meow meow’): chemical, pharmacological and clinical issues

Abstract: Within the UK, diffusion of mephedrone may have been associated with an unprecedented combination of a particularly aggressive online marketing policy and a decreasing availability/purity of both ecstasy and cocaine. Mephedrone has been recently classified in both the UK and in a number of other countries as a measure to control its availability. Following this, a few other research psychoactives have recently entered the online market as yet unregulated substances that may substitute for mephedrone. Only inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
246
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(265 citation statements)
references
References 38 publications
9
246
0
10
Order By: Relevance
“…The rapid rise in popularity of mephedrone may reflect growing user dissatisfaction with the purity and availability of MDMA (ecstasy) or its chemical precursors and cocaine. Mephedrone appears to be used by several population groups, including people involved in the dance and music scene, as well as mainstream young adults, and adolescents (Schifano et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid rise in popularity of mephedrone may reflect growing user dissatisfaction with the purity and availability of MDMA (ecstasy) or its chemical precursors and cocaine. Mephedrone appears to be used by several population groups, including people involved in the dance and music scene, as well as mainstream young adults, and adolescents (Schifano et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Users describe this feeling as the drug being very "moreish", meaning that it causes the user to want to ingest more shortly after use [11,28,61], and call taking multiple doses in succession "fiending" [62].…”
Section: Addiction and Withdrawalmentioning
confidence: 99%
“…It has been reported that mephedrone is sometimes sold in some countries as either ecstasy or 'synthetic' cocaine (Deluca et al, 2009;Schifano et al, 2011). Furthermore, it may be found mixed with adulterants, such as caffeine, paracetamol and even cocaine, amphetamine and ketamine (Camilleri et al, 2010), as well as with other methcathinones (as revealed by information supplied to the National Programme on Substance Abuse Deaths by coroners -see below).…”
Section: Chemistrymentioning
confidence: 99%